THE STRUCTURE AND COMPONENTS OF THE DEVELOPMENT OF GENDER CULTURE AMONG STUDENTS (Scientific journal of the Fergana State University, 2023)
The article substantiates the need for different countries to develop their own models of higher education system and its modernization in the context of globalization, as an imitation of foreign models is unproductive and risky. The Higher School may get a chance to become a highly significant institution of society, through updating goals and objectives of its activities, technologies and organizational formats.